UGGT1 retains proinsulin in the endoplasmic reticulum in an arginine dependent manner - Cho, Jaeyong; Hiramoto, Masaki; Masaike, Yuka; Sakamoto, Satoshi; Imai, Yoichi; Imai, Yumi; Handa, Hiroshi; Imai, Takeshi (Biochemical and biophysical research communications, 2020)
We sought to clarify a pathway by which L- and dD-arginine simulate insulin secretion in mice and cell lines and obtained the following novel two findings. (1) Using affinity magnetic nanobeads technology, we identified that proinsulin is retained in the endoplasmic reticulum (ER) through UDP-glucose:glycoprotein glucosyltransferase 1 (UGGT1) when arginine availability is limited. (2) L- and d-arginine release proinsulin from UGGT1 through competition with proinsulin and promote exit of proinsulin from the ER to Golgi apparatus. The ability of arginine to release proinsulin from UGGT1 closely correlates with arginine-induced insulin secretion in several models of β cells indicating that UGGT1-proinsulin interaction regulates arginine-induced insulin secretion. [Display omitted] •UGGT1 binds to proinsulin in the absence of arginine.•Arginine competes with proinsulin and binds to UGGT1 in the ER.•Released proinsulin moves to Golgi apparatus and secretory vesicles to secrete.